Desain Model Rumah Moveable Layak Huni dan Terjangkau - Muhammad Fauzan (Pusat Riset dan Inovasi Nasional, 2024)
The backlog of housing in D.I. Yogyakarta has continued to increase year after year. One potential solution to address this issue, considering the high property prices and relatively low regional minimum wage (UMR), is affordable and livable moveable housing. The research was condusted using qualitative methods, surveying several respondents residing in three sub-districts characterizwd by the dense infrastruture, non-agrarian activities, and high land prices. The model of the moveable house, with funvtional spaces for a bedroom, a bathroom, and kitchen, has capacity for two occupants. Moveable livable houses were highly favored by respondents, with a preference rate of 92,3%.